MRI features of AIDS with neurosyphilis - Mei-Ji REN; Li LI; Jing ZHAO; Hong-Jun LI (Yixue xinzhi zazhi)
Objective To investigate the MRI manifestations of AIDS associated with neurosyphilis and improve the understanding of this condition.Methods Data showing the imaging characteristics and clinical manifestations in patients with clinically proven AIDS associated with neurosyphilis in Bei-jing You’an Hospital Affiliated of Capital Medical University were collected and analyzed retrospectively.Results A total of 32 patients were included and a total of 29 lesions were found. The location of le-sions was: temporal lobe 7 cases (24.14%), basal gangli 6 cases (20.69%), frontal lobe 6 cases (20.69%), parietal lobe 3 cases (10.34%), occipital lobe 3 cases (10.34%), centrum semiovale 2 cases (6.90%) and cerebral atrophy was present in 2 cases (6.90%). According to the site of TP invasion and clinical mani-festations, the types of cases were as follows: 9 asymptomatic cases (28.12%), 2 meningeal cases (6.25%), 5 meningeal vascular cases (15.62%), 15 parenchymal cases (46.88%) and 1 gumma case (3.13%). After injection of Gd-DTPA, gyria-enhancment was detected in meningal neurosyphilis, lamella and gyria-enhancment was found in meningovascular neurosyphilis, while irregular enhancing was noted in the cerebral gumma. Cerebral atrophy was manifested in a patient with general paresis of the insane. The symptoms improved after anti-syphilis treatment.Conclusion AIDS with neurosyphilis has atypical MRI manifestations. Comprehensive analysis of imaging data and laboratory examination is helpful to assist in early diagnosis of neurosyphilis.